On the gravitational mass of antiparticles, the gravitational energy shift of spectral lines, and the principle of equivalence - Thieberger, P. (Societa Italiana Di Fisica, 1965)
Fil: Thieberger, P. Comisión Nacional de Energía Atómica; Argentina